Development of Wordwall-Assisted Educational Game Media on Fractions to Improve Mathematical Literacy in Elementary School Students - Ridwan Syaidi Ridwan; Tustiyana Windyani; Dadang Jaenudin (Universitas Suryakancana, 2026)
This study aims to develop Wordwall-assisted educational game media on fraction material to improve the mathematical literacy of elementary school students. The low scores of Indonesian students in international assessments such as PISA 2022, combined with the abstract nature of fraction concepts and the dominance of teacher-centered conventional instruction, highlight the urgent need for innovative, technology-integrated learning media. This research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects included material, media, and language expert validators, 15 teachers for feasibility testing, and 38 fifth-grade students at SDN Batukarut, Sukaraja, Sukabumi, as the experimental group. Data were collected through expert validation sheets, teacher and student response questionnaires, and mathematical literacy tests. Results indicate that the developed Wordwall-based educational game achieved a